Sobre Soluções Positivas para uma Classe de Equações Elípticas Semilineares - Pontes, Enieze Cardoso de (2014)
In this work, we study the existence of positive solutions for a class of semilinear elliptic equations in a smooth bounded domain, with Dirichlet boundary condition and non-linear terms changing sign as well as with small perturbations. In order to obtain the positive solution, in the first case we use a version of the Mountain Pass Theorem in Ordered Banach spaces. In the second case, the main term is under assumptions that guarantee the application of the usual Mountain Pass Theorem and the perturbation term does not require any hypothesis.